Uso e manejo tradicional de cactaceae em uma região do semiárido da Paraíba - Pedrosa, Kamila Marques (2018)
The species in the Cactaceae family have physiological adaptations to arid and semiarid climates, the species are available in these regions for use by animals and traditional people. Over time, human populations have involuntarily managed cactuses, preserving selected individuals who have distinct phenotypes and are economically viable, and meet their needs. This study aimed to record the uses and management of Cactaceae species. The present study was carried out in the rural communities Caiçara, Tapera, Rio Direito e Caruatá de Dentro, State of Paraiba, Northeast Brazil. In order to obtain the information, a semi structured questionnaire was applied with 44 informants (30 men and 14 women). The questionnaire contained questions about the use and management that the residents carried out of the Cactaceae species. Six species have been registered: Pilosocereus gounellei, Cereus jamacaru, Melocactus zehntneri, Pilosocereus gounellei¸ Tacinga inamoena, Tacinga palmadora,framed in the utilitarian categories: food, fuel, construction, forage, medicinal, technology and others. 45% of the informants perform the management (in-situ and ex-situ), 54% do not practice any type of management. Residents are motivated to manage the species of Cactaceae due to the importance that the resource offers to the communities. The techniques used for burning individuals become worrying, since the protection does not occur on the part of all the people of the community.